Pengaruh Beban Kerja, Stres Kerja, Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Sumber Indah Perkasa Tulang Bawang Kebun Sungai Buaya Estate (SBYE) - Nurviana, Wiwin; Lelawati, Nina (Universitas Muhammadiyah Metro, 2022)
WiwinNurviana. 2021. “The Effect of Workload, Work Stress, Work Environment and Compensation on Employee Performance at PT. Sumber Indah Perkasa Tulang Bawang Sungai Buaya Estate (SBYE)”. Thesis. Management Studies Program, Faculty of Economics and Business. University of Muhammadiyah Metro. Supervisor (1) H. Suwarto, S.E., M.M. (2) Dr. H. Febriyanto, S.E., M.M. This research was conducted at PT. Sumber Indah Perkasa Tulang Bawang Sungai Buaya Estate (SBYE) is a company engaged in oil palm plantations. Where its operational activities require competent workers, therefore human resource management must also be improved. This research was conducted on employees of PT. Sumber Indah Perkasa Tulang Bawang Sungai Buaya Estate (SBYE). By distributing questionnaires in the form of questions about Workload, Work Stress, Work Environment, and Compensation for Employee Performance. Then processed with SPSS version 21 with the classical assumption test approach with the linearity normality method, homogeneity. This study uses quantitative methods with multiple linear regression analysis, partial test, F test, determination to determine the effect of workload, work stress, work environment and compensation on the performance of employees of. The results of this study indicate that simultaneously workload, work stress, work environment and compensation on employee performance. Research specifically shows that workload has a positive and significant effect, work stress has a positive and significant effect, the work environment has a positive and significant effect, and compensation has a positive and significant effect on employee performance. Keywords: Workload, Work Stress, Work Environment, Compensation, Employee Performance.